The Effectiveness of Moringa oleifera L. Seeds as A Biocoagulant in Reducing Liquid Waste of The Soft Drink Industry - A, Asriani; M Aras, Neny Rasnyanti (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2020)
The liquid waste of the soft drink industry usually uses as raw materials in the form of sugar as a flavoring with glucose as the main raw material. Thus, it is not surprising that this waste contains a lot of organic materials. Companies generally use an aerobic system to control contamination that may occur due to the high organic content contained in waste. The purpose of this study was to provide another alternative in controlling liquid industrial waste pollution by using natural coagulants in terms of reducing COD, TSS, turbidity, and pH with various doses of moringa seed coagulants. This research was conducted by finding the optimum dose of coagulant in reducing COD, TSS, turbidity and pH values. Based on the research results, the optimum dose obtained was 1.5 grams of moringa seed coagulant which can reduce TSS by 89%, turbidity 65% and COD by 88%. From these results it can be concluded that using the moringa seed coagulant can improve the quality of liquid waste in the soft drink industry.Keywords: moringa seeds, biocoagulant, liquid waste industry, COD, TSS